Tidlig-neolitiske anlæg ved Rustrup - Fischer, Christian (Kuml, 1975)
Early Neolithic structures at Rustrup In the period 1971-1974 Silkeborg Museum excavated two Early Neolithic structures of the Funnel Beaker culture at Rustrup about 10 km south of Silkeborg (fig. 1). STRUCTURE I The structure lay under a completely demolished barrow from either the Stone or the Bronze Age and consisted of an east-west oriented rectangular stone setting measuring 13 X 6 m (fig. 2 and 3). The stones, which mainly lay in a single layer, varied in size between 20 and 50 cm. Between them was a quantity of burnt flint. The setting seemed to consist of two parts, but this may be due to later disturbance. Its edge was marked to the north, west and east by oblong stones, lying close together. From the north-west corner, curving to the west, was a row of stones which is thought to be part of the kerb of the barrow. Between the subsoil and the setting was a 10-20 cm thick layer of brown-spotted leached sand containing many charcoal fragments and particles. From this layer and into the subsoil could be separated two rows of stake-holes, possible post-holes, a wall trench, a grave, and a single pit (fig. 4). Stake-holes At the west end of the structure were two staggered parallel rows of stakeholes. A connection between the two rows could not be demonstrated on account of disturbance. The diameter of the stakes was 7-8 cm. Post-holes A row of round and oval brown marks containing charcoal particles is thought to represent post-holes, but this identification is not certain. Wall trench At the east end of the structure was a trench, strongly concave to the west. Its length was 4.9 m, width 1.05-0.80 m and depth 1.20-1.08 m. It contained distinct traces of posts about 20 cm in diameter, which stood dose together and were supported by stones about 10-30 cm in length. Grave A In the middle of and immediately under the north part of the setting was an ill-defined brown patch of soil with an angular outline; the width varied between 10 and 30 cm and the thickness was less than 10 cm. Within this area were found inter alia the multi-faceted axe (fig. 35) and the amber ornament (fig. 36). Other indications of a burial such as a rim of stones were not observed. Pits Eight pits were found in the subsoil, partly under the structure. All except one (pit A) were empty. This pit seems to be linked to the structure, since a potsherd which it contained derived from a complex of sherds in the layer between the stones and the subsoil. Artefacts The layer between the stone setting and the subsoil yielded a number of artefacts, mostly pottery but also amber beads, an amber ornament, flint implements, and a multi-faceted axe of greenstone, among other objects. The artefacts were in most cases found within three areas under and between the stones of the setting: at and just outside the south-western corner, in the centre in the area marked grave A and in the middle of the west side of the wall trench. A few isolated finds were also made. The objects from the south-west corner comprise potsherds, clay discs, a transverse arrowhead and two amber beads. The pottery comprises fragments of decorated and undecorated vessels. About half the sherds could be united to form a single base and the remainder to small surfaces deriving from 4-6 vessels. Two of these complexes derive from small beakers with covering ornament and different stab-marks (fig. 13 and 29), and the third from a larger funnel beaker with four horizontal rows of cord impressions under the rim and short vertical cord impressions collected in groups under the neck (fig. 14). Three fragments seem to derive from the same clay disc (fig. 16). Other finds were a transverse arrowhead (fig. 32) and at the south-west corner of grave A a short and a long cylindrical amber bead. It could not be determined with certainty whether a number of the objects found in this area had been deliberately placed there or whether they should be regarded as adventitious material from the settlement, which was otherwise only slightly represented in the structure. Whatever the case, the stratigraphy shows that the artefacts are coeval with or perhaps older than the structure. The other artefact area lay just under the northern part of the stone setting. Within an area measuring 4 m2 the following objects were found: a multifaceted axe of greenstone (fig. 35), a figure-of-eight amber ornament (fig. 36), a short cylindrical amber bead, two transverse arrowheads (fig. 32), a flint sickle, and three flint chips. The position of the various items is shown in fig. 4. All except the amber bead lay within the angular area called grave A and the assemblage must be grave goods. No traces of a skeleton were found, but this is not surprising when the nature of the soil is taken into account. About 1 m west of the centre of wall trench A, just under the stone setting, were two lugged beakers (fig. 9a-b), standing about 20 cm apart. No traces of a grave were found around them; they may be burial goods, but it is also possible to regard them as votive objects. 2 m south of the spot where the two beakers stood, at the top of the wall trench and in front of it to the west, the fragments of a large lugged vase were found (fig. 11). It was not possible to decide whether this was intrusive settlement material or, perhaps with the two lugged beakers, an integral part of the find. The same applies to the neck of a collared flask (fig. 15) which lay mid-way between grave A and the two lugged beakers. Artefacts which must be considered intrusive settlement material are very modestly represented apart from the possible element at the south-western corner. Only a few scattered potsherds, the edge corner of a four-sided, polished, thinbutted axe, a couple of scrapers (fig. 33a-b) and a flake borer can be characterized as such, possibly with the addition of two blade sickles (fig. 34a-b) which lay between the stones in the area above grave A. Dating Two charcoal samples were extracted from wall trench A and submitted to C14 determination at the National Museum. One sample consisted of charcoal found in a circle comprising the periphery of a post about 20 cm in diameter, placed in the trench. This must indicate quite accurately the time at which the post was erected - 2960 ± 100 B. C. The other sample was recovered from the post traces seen in section fig. 6 and gave 3020 ± 100 B. C. All dates are given in conventional C14 years. The two lugged beakers, which stood under the stone packing up to the wall trench A, are well known type specimens within the non-Megalithic group of the Funnel Beaker culture, which must be dated to period C of the Early Neolithic (3). The same applies to the ornamented pottery from the south-west corner of the structure and the fragments of the lugged vase at the south end of wall trench A. The other ceramic material, which must be considered coeval with the structure and certainly no younger, does not contradict this dating. The multi-faceted axe has until recently not been found in certain association with datable artefacts in Denmark, but nearly a dozen graves have shown that a dating to Early Neolithic C is most likely, with respect to the type in question here (4). A new grave find from Dragsholm shows that the multi-faceted axe in another form than the Rustrup axe is found with pottery of Early Neolithic A type. The Dragsholm grave is C14 dated to 2890 ± 100 B. C., i. e. slightly later than the Rustrup structure (5). The Rustrup structure’s C14 datings indicate, like other C14 datings (6), that the schematic division of Early Neolithic into consecutive A-, B- and C-phases applied to the whole of Denmark, cannot be considered universally valid. Reconstruction of events If one attempts to reconstruct the course of events in the structure it is easiest to divide it into three phases, the first (I) comprising what was found under the stone setting, the second (II) the stone setting and the third (III) the erection of a burial mound over the area. Phase I, which is stratigraphically prior to the stone setting, comprises trench A, the post-holes and probably the stake-holes, grave A and the objects found under the stone setting. The deep wall trench defines the area very clearly to the east. Whether the posts of which there were traces in the charcoal with the other not particularly well-defined post-holes and stake-holes to the west were originally part of a single wooden construction could not be determined by excavation, but the occurrence of charcoal in the area covered by the stones suggests that some kind of wooden construction, which was later burnt, may have been present. Within this area, between the wall trench and the stake-holes, grave A was laid direct on the soil surface. It was not manifest in any other way than by an angular brownish patch which to the south and east defined the occurrence of a series of artefacts: the multi-faceted axe, the amber ornament, the amber bead, the transverse arrowheads, the flint sickle and flint chips, which must have been grave goods for a man. The two lugged beakers (and possibly the lugged vase), which stood near the wall trench, are 5 m from the east end of grave A and have hardly any connection with this, unless they were placed as votive offerings in the structure which then only contained grave A. A more likely explanation is that they comprised the grave goods of yet another grave, which like grave A was placed direct on the ground without any kind of excavation. It cannot be determined with reasonable certainty whether any of the other artefacts are grave or votive goods or merely settlement intrusions. Phase II comprised the covering of phase I with stones. It is not very likely that this would have given rise to a prominent barrow. Phase III comprised the erection of a burial mound about 12 m in diameter above the structure in the Stone or Bronze Age. So far, structure I seems to be without parallels in Denmark. The covering of ground graves is a common feature in Central and North Jutland (7), but the cover is confined to the grave area itself. It is not an unknown phenomenon in the Funnel Beaker culture that a grave must be perceived in two phases, the first comprising the actual burial within a wooden construction and the other the destruction of this wooden construction perhaps by setting fire to it, and covering the area with stones (8-10). STRUCTURE II This structure was excavated in January 1974. It lay immediately west of the area excavated in connection with structure I and only 6 m from the west end of the stone setting. It was manifest before excavation only by stones 10-20 cm long brought up by the plough; no elevation was apparent. The structure appeared as an approximately U-shaped feature oriented northsouth, opening to the south. In the middle of the opening was a post-hole. The northern two-thirds of the structure was covered by a 5-10 cm thick concentrated fire layer consisting of leached white sand with a very large content of charcoal. The southern third was not covered in this manner and the boundary to the fire layer was relatively sharp and perpendicular to the long axis of the structure. The absence of a fire layer here may be due to ploughing. In the fire layer there were traces of many stones, and a few still remained, mainly in the north-western corner where two large stones afforded protection from farm implements. These two stones and traces of stones of the same size could be followed in a close row behind the north end of the structure and along the west side of the northern half (fig. 37). To decide whether structure II had a direct connection with structure I, the area between them was investigated without any traces of structure or artefacts of any kind being found. Artefacts In the fire layer a number of artefacts, including pottery and flint, were found, with many fragments of clay daub. The artefacts were randomly arranged, fragments of the same vessel, for example, being found throughout the fire area. Outside the fire layer practically no artefacts were found. A solitary polished, thin-butted flint axe (fig. 4 7) was found ex situ just outside the north-west corner. The pottery from the fire layer comprised 153 sherds; 60 of these were decorated and could be united to represent three vessels. In one of these, which is decorated with a horizontal moulding near the rim and under this four horizontal cord impressions, the neck is almost intact (fig. 40). A number of the largest undecorated sherds possibly represented the base of this vessel. The two other decorated segments are from small beakers furnished with various stab-marks, in both cases in a pattern covering the surface (fig. 41 and 44). Among the sherds were the remains of two small clay discs, one with a smooth rim and the other with stab-marks on the rim (fig. 45a-b and 46). The other decorated sherds are small fragments of vessels. The flint inventory comprises three blade scrapers (fig. 48a-b), a combined borer and scraper with polishing marks, the edge of a transverse arrow head, two blade sickles (fig. 49a-b), three flint chips with polishing and about 20 pieces of flint swarf. Many pieces of clay daub were present. Dating and cultural attribution The charcoal sample, taken from the fire layer, yielded a C14date of 2970 ± 100 B. C., which agrees within the limits of the method with the dating of structure I. The pottery is identical in shape and decoration to that from structure I, and is referred to the north Jutland non-Megalithic group phase C. The other objects of flint present in the fire layer do not contradict this dating and placing. Interpretation of structure II The structure is interpreted as the ground plan of a U -shaped house opening to the south. Behind to the north and perhaps along the sides stones 50 cm long supported the walls which stood in the shallow depressions. The many burnt fragments of clay show that the house had been daubed. The inside width was 1.55 m and the inside length 4 m. A fire layer shows the extent of the house. It is tempting to interpret the house as a grave structure, not least because of its situation in relation to structure I. It lay only 6 m from the west end and in direct continuation of structure I, perpendicular to its long axis. The narrow width of the house speaks for an interpretation along these lines as does the fact that it has been burnt and covered with stones. The stone covering can, however, have derived from collapsed walls and roof. It also seems strange that artefacts do not occur outside the area of the structure, although the plough has gone deep. The fact that the artefacts from the fire layer seem to suggest settlement inventory indicates a dwelling, so unfortunately no final choice between the two interpretations can be made. Appendix: Two previously unpublished earth graves from Central Jutland The earth grave at Hedegårde lay 2 km south of Rustrup. It was found in 1968 and excavated by C. L. Vebæk of the National Museum after it had been partly excavated by the farmer. The site of the grave was a broad depression between two hills; the field itself is flat and sandy. Before excavation a low oblong elevation had revealed the spot. The blanket of stones which covered the grave had an extent of 5 m east-west and 2.25 m north-south. It had been rather flat, consisting of stones about 10 cm in diameter in 2-3 layers. Between the stones there had been a little burnt flint. When the stones were removed, two large funnel-shaped excavations were found in the yellow-brown subsoil. These excavations measured 1.4-1.6 m in width above and 0.2-0.4 m below. Each contained a post, the diameter of which on the evidence of the stone packing must have been about 30 cm. Mid-way between the two excavations, within a small area of ½ X ½ m, the farmer had found 40 amber beads on a bed of burnt flint. The entire find of amber beads comprises at least 70 pieces, 13 of which were lumpy, 44 cylindrical, and 13-16 fragments. The beads, which were the only objects found in the grave, were of a common type known from both Early and Middle Neolithic (fig. 51). The grave corresponds very closely to the Early Neolithic ground graves with tent-shaped superstructure (13). This find from Hedegårde seems to confirm the course of events for these tent-shaped graves: the deceased with grave goods, here amber beads, was laid to rest on a bed of burnt flint, over which was raised a tent-shaped superstructure, the ridge pole of which rested on the heavy posts sunk into the subsoil at each end of the grave. After a period the superstructure was removed and burnt and the area covered with stones. In 1960 Silkeborg Museum excavated a presumptive grave at Anebjerggård, Linå, about 8 km east of Silkeborg. A stone setting much disturbed by ploughing, it measured 5 X 4 m and was constructed of stones 20-40 cm in diameter, placed irregularly in several layers. When the stones were removed a small pit was discovered under the structure. From this pit were recovered fragments deriving from a lugged flask with long narrow neck and vertical plastic moulding on the belly (fig. 52a). In addition, the grave contained the end of a dagger handle (fig. 526) and a piece of unworked amber. The flask may be dated to Early Neolithic C and has its closest parallels in the south Danish area. Christian Fischer